2005
DOI: 10.1308/1478708051540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of introduction of digital radiographic techniques on pre-operative templating in orthopaedic practice

Abstract: Surgeons should be aware that introduction of digital techniques of radiograph acquisition may reduce the magnification of the film and, therefore, reduce the accuracy of pre-operative templates supplied by the manufacturers of implants, resulting in incorrect selection of implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Bayne et al report a magnification factor of 120 ±5%; in contrast, White and Shardlow found a factor of 97 % for digital templating compared with 115-120 % for analogue templating [9,17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bayne et al report a magnification factor of 120 ±5%; in contrast, White and Shardlow found a factor of 97 % for digital templating compared with 115-120 % for analogue templating [9,17].…”
Section: Discussionmentioning
confidence: 93%
“…Prior to the introduction of digital radiography, planning was performed using hard-copy radiographic films and traditional prosthetic overlays with fixed magnification factors of 115 % or 120 % [4,9,10]. The introduction of digital radiography included the development of software programs to enable direct size selection planning on the digital image [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most publications in leading orthopaedic journals have focused on the description and methodology involved in using the software [1] and, to the best of our knowledge, only one report on an analysis of its accuracy and friendliness has been published in the English literature [19,20]. This study was conducted to evaluate the utility and precision of digital preoperative templating for primary, conventional total hip arthroplasty for osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Several software packages for preoperative templating on digital images have been developed [1,19,20]. Consequently, digital preoperative planning should be as useful and precise as the traditional method of acetate templates superimposed on standardised radiographs [8].…”
mentioning
confidence: 99%
“…14,15 Digital templating offers a way to avoid these errors with quicker, more cost-efficient templating that can be easily stored for future reference. 16 It has also been shown that the accuracy of pre-operative digital templating in knee and hip arthroplasty meets or exceeds that of analogue templating, thus giving more support for the use of entirely digital techniques.…”
Section: Introductionmentioning
confidence: 99%